Diversity and heterogeneity in human breast cancer adipose tissue revealed at single-nucleus resolution - Tang, Lina; Li, Tingting; Xie, Jing; Huo, Yanping; Ye, Jianping (Frontiers in Immunology, 2023)
There is increasing awareness of the role of adipose tissue in breast cancer occurrence and developments, but no comparison of adipose adjacent to breast cancer tissues and adipose adjacent to normal breast tissues has been reported. In this study, we used single-nucleus RNA sequencing (snRNA-seq) to analyze cancer-adjacent and normal adipose tissues from the same breast cancer patient to characterize heterogeneity. SnRNA-seq was performed on 54513 cells from six samples of normal breast adipose tissue (N) distant from the tumor and tumor-adjacent adipose tissue (T) from the three patients (all surgically resected). Significant diversity was detected in cell subgroups, differentiation status and, gene expression profiles. Breast cancer induces inflammatory gene profiles in most adipose cell types, such as macrophages, endothelial cells, and adipocytes. Furthermore, breast cancer decreased lipid uptake and the lipolytic phenotype and caused a switch to lipid biosynthesis and inflammatory state in adipocytes. And the in vivo trajectory of adipogenesis revealed distinct transcriptional stages.Breast cancer induces reprogramming across multiple cell types in breast cancer adipose tissues. Cellular remodeling was investigated by alternations in cell proportions, transcriptional profiles, and cell-cell interactions. This study facilitates exploring of breast cancer biology and enables identification of novel biomarkers and therapy targets.